Study of optimum conditions for formation of phenolic azoeimine - Adel Saeed Azzoz; Mohammed M. Al-Nuami (College of Education for Pure Sciences, 2009)
Abstract The main object of the study is concerned with studying optimal conditions for the azo dyes formed by the reactions of the mother compound 2,4-dihydroxy benzaldehyde and its twelveth imine derivatives in the forms of oxime and Schiff bases by the spectrophotometric method, at different experimental pH,s. This study include several experimental factors as volume of reagent, best volume of a Na2CO3 base to obtain the desired pH, order of addition, development time with stability period and optimal wavelengths of the dye complexes. The study comes to a conclusion that each of the experimental factors just mentioned depends primaraly on the chemical structure of imines. The stoichiometry for all formede dyes under study, are determined by using a mole ratio method and founded to be of types 1:1.